The Effectiveness of Natural Plant Growth Regulators on the Germination of Expired Green Eggplant (Solanum melongena L.) Seeds: Efektivitas ZPT Alami Terhadap Perkecambahan Benih Terung Hijau (Solanum melongena L.) Kadaluarsa - Haris Septiawan; Primadiyanti Arsela; Ardaniah Ardaniah (Universitas Nusa Bangsa, 2026)
Green eggplant seeds (Solanum melongena L.) have a relatively short storage life and are prone to deterioration in viability and vigor due to aging during storage. One approach to restore the physiological quality of expired seeds is seed invigoration using natural plant growth regulators (PGRs). This study aimed to evaluate the effectiveness of several natural PGR sources, namely coconut water, shallot extract, and aloe vera extract, as well as soaking duration, on the viability and early growth of expired green eggplant seeds. The experiment was conducted at the experimental field of the Faculty of Agriculture and Digital Business, Universitas Muhammadiyah Kalimantan Timur, using a factorial Randomized Block Design: type of invigoration material and soaking duration (2 and 4 hours), with three replications. Observed parameters included germination percentage, germination time, and seedling height at 7–10 days after planting (DAP). The results showed that invigoration materials and their interaction with soaking duration significantly to highly significantly affected most observed parameters. Aloe vera extract consistently produced the best results in accelerating germination and enhancing seedling height across all observation periods. These findings indicate that expired green eggplant seeds still possess recoverable physiological potential when treated with appropriate, low-cost, and environmentally friendly natural invigoration materials.